The relationship between leadership style and employee engagement at employee provident fund (EPF) / Nur Syasya Syazwina Azman - Azman, Nur Syasya Syazwina (Faculty of Business and Management, 2018)
The purpose of this study is to study the relationship between leadership styles towards employee engagement in Employee Provident Fund (EPF). There are two types of leadership styles which is transformational leadership and transactional leadership. These two types of leadership will measure the most affecting factor towards employee engagement at Employee Provident Fund (EPF). In this research, the researcher chooses simple random sampling as the method. Consequently, 82 questionnaires were distributed to the employees in Employee Provident Fund (EPF) and greatly the total returned is also 72. Then, the result of the questionnaire collected was analyzed by using Statistical Package for Social Science (SPSS) 20.0 and were further analyzed using frequency analysis, reliability, regression analysis and descriptive analysis.